1986
DOI: 10.1099/00221287-132-7-2035
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Actin Localization during Bud and Hypha Formation in the Yeast Candida albicans

Abstract: Stationary phase cells of Candida albicans can form either a bud or a hypha, depending upon the pH of the medium into which they are released. At low pH, cells form an ellipsoidal bud and at high pH, cells form an elongated hypha. By staining cells with rhodamine-conjugated phalloidin, we have compared the dynamics of actin localization during the formation of buds and hyphae. Before evagination, actin granules were distributed throughout the cytoplasmic cortex in both budding and hypha-forming cells. Just bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
65
0
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 18 publications
8
65
0
2
Order By: Relevance
“…Polarization of the actin cytoskeleton at the tips of hyphae was reported previously and is probably required for hyphal elongation (Anderson and Soll, 1986;Yokoyama et al, 1990). We observed that the actin polarization at the hyphal tip appeared 30 min after hyphal induction in G 1 cells, ϳ70 min before SPB duplication, DNA replication, and chitin ring formation, and that it persisted throughout the cell cycle (Figures 3B, bottom; and 4B).…”
Section: Hyphal Tip-associated Polarization Of Actin Cytoskeleton Persupporting
confidence: 53%
See 3 more Smart Citations
“…Polarization of the actin cytoskeleton at the tips of hyphae was reported previously and is probably required for hyphal elongation (Anderson and Soll, 1986;Yokoyama et al, 1990). We observed that the actin polarization at the hyphal tip appeared 30 min after hyphal induction in G 1 cells, ϳ70 min before SPB duplication, DNA replication, and chitin ring formation, and that it persisted throughout the cell cycle (Figures 3B, bottom; and 4B).…”
Section: Hyphal Tip-associated Polarization Of Actin Cytoskeleton Persupporting
confidence: 53%
“…Hyphal-associated polarization of the actin cytoskeleton is located exclusively at the tip of each hypha (Anderson and Soll, 1986). It coexists with the cell cycle-regulated actin assemblies in the apical cells of each hypha ( Figure 4B), and both contribute to cell shape.…”
Section: Potential Mechanisms For Hyphal-associated Polarization Of Amentioning
confidence: 99%
See 2 more Smart Citations
“…The actin cytoskeleton of the fungal pathogen C. albicans plays a key role in morphogenesis and hyphal formation (1,4,5,32,41,55,58). In yeasts, this cytoskeleton is comprised of cortical actin patches found at sites of polarized growth and actin cables that serve as tracks for secretion of vesicles to sites of polarized growth (11,45,46).…”
mentioning
confidence: 99%